Recovery : a journey and a destination : a phenomenological study of older people recovering at home after surgery : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, Palmerston North, New Zealand - Wootton, Rayna Margaret (Massey University, 2002)
As world populations age there are more older people having surgery. Hospitalisation for surgery is commonly for the day only or short stay, so most of the period of recovery is spent at home where the older person lives either alone or with a spouse / partner. The purpose of this study was to understand the phenomenon of recovery at home for older people who have had surgery. Thirteen older people, ten men and three women, were interviewed after they returned home following surgery. Four interviews were conducted over an eight week period. Participants were aged between 69 and 88 years with most being in the 70-80 years age group. Hermeneutic phenomenology underpinned by the work of Heidegger was used to examine the phenomenon of recovery as experienced by the participants. The essence of recovery was revealed as enduring my world, caring for and about myself, relating to people and place in my world, and continuing my life. These arose out of four themes -disturbance of one's being-in-the-world; being concerned with; being-with others, and recapturing being-in-the-world. The four lifeworld existentials of lived time, lived body, lived other and lived space were used to illustrate the nature of recovery for the older person. Lived time was of particular significance. Age per se was not perceived by participants as a major factor affecting their recovery. Being at home, the effects of surgery on the body and on daily life, being actively involved in their recovery, the support of others, and knowledge and understanding, were significant in the participants' experience of recovery. Recovery was revealed to be both a journey and a destination.
Keywords: Older people; Elderly; Recovery; Post-surgery recovery; Patients; Personal narratives; New Zealand; Home care